The Overwhelming Postsplenectomy Sepsis: Role of Plastic Surgeon - Marta Starnoni, MD; Marco Pappalardo, MD, PhD; Caterina Marra, MD; Massimo Pinelli, MD; Giorgio De Santis, MD (Plastic and Reconstructive Surgery, Global Open, 2023)
Summary:. The overwhelming post-splenectomy infection (OPSI) is a feared late complication of splenectomy, with high morbidity and a mortality rate of up to 50%. Although the management of this syndrome is the duty of clinical physicians, the interest of plastic surgeons in OPSI is related to the injury that can occur in tissues with an end circulation, such as the limb extremities, nasal tip, and lips. In the management of OPSI, surgical techniques are not highlighted. The role of the plastic surgeon can be fundamental for the prevention of further extension of the necrotic tissue, improving as much as possible the vascularization around it. Moreover, a critical role in the management of OPSI is avoiding superinfection of the necrotic areas by combining different techniques and methods, such as surgical debridements, negative pressure wound therapy, and conservative treatment. Last but not least, functional and aesthetic restoration of the injured parts is of paramount importance for the final outcome. In this article, we describe the management of two unvaccinated patients with necrosis of the extremities after OPSI.